Design formulae for predicting the stress concentration factors of concrete-filled T-joints under out-of-plane bending. (December 2020) - Matti, Feleb N.; Mashiri, Fidelis R.
Abstract: An experimental study was carried out on seven square hollow section (SHS) T-joint specimens with concrete-filled chords to determine the stress concentration factor (SCF) at the hot spot locations. A parametric study was then carried out on concrete-filled SHS-SHS T-joint models using ABAQUS software to determine the numerical stress concentration factor (SCF) at the hot spot locations. Sixty SHS-SHS concrete-filled T-joints were modelled and analysed under out-plane bending on the brace to study the effect of the non-dimensional parameters on the SCFs. The numerical SCFs from FEA were validated as comparable results of SCFs were obtained between the numerical and experimental studies. Proposed design formulae were developed for determining the SCF in SHS concrete-filled T-joints under out-of-plane bending. This was achieved by carrying out non-linear multiple regression analysis using the results of the parametric study. The maximum SCF in SHS T-joints with concrete-filled chord subjected to out-of-plane brace bending commonly occurred along lines A, B and C.